Kamuana in Nyando, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Photos taken at the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) benchmark site Nyando Kenya.